Perception of Woman in Proverbs in Terms of Gender - Hanife Nâlân Genç (Folklor/Edebiyat, 2018)
In the course of time, observations, experiences, and impressions about the general attitudes and behaviors of an individual become stereotyped and turn into the words which characterize a certain situation and/or events. These words reflect the viewpoint of one person against another, the world, and the society of which s/he is a member. From this perspective, proverbs and idioms contain the viewpoints, evaluations, and judgements about concepts, situations, and facts which societies develop within the context of socio-cultural issues. This research is based on the general screening model and emphasizes the perception of women in terms of gender in proverbs. The research analyzes how women are perceived in individual, domestic and social life or how they are made to be perceived by society. It is clearly seen from the research that proverbs and phrases about women are frequently evaluated within a domestic sphere and familial relationships. The perspective of a society toward women becomes integrated with the roles of women in social and domestic life. The gender perception of women in society has religious, economic, political, social, and cultural differences. There are also different perceptions about women’s sexuality, education, and familial bonds. Within this criteria, the thoughts and judgements about the concept of women in proverbs are either affirmative, negative, or a combination of the two. This research finds that the situation of women in proverbs is mostly determined by a brother, father and/or a husband in a male dominated famil